MODEL PENGEMBANGAN STAF YANG EFEKTIF DI LEMBAGA PENDIDIKAN ISLAM - Maulidia Maulidia; Nur Azizah Fatiati; Ahmad Sulaiman Mahbubi (Tarbawi, 2023)
An effective staff development model in Islamic education\al institutions is crucial to improving the quality of education and achieving institutional goals. In this article, we will examine the key elements of creating an effective staff development model. Factors such as identification of training needs, improvement of pedagogical skills, and engagement in professional development activities were integral to the design of the model. Integrating Islamic values and an in-depth understanding of the context of Islamic education are important points in designing this model. Apart from that, leadership support, performance evaluation, and career development are also taken into account. It is hoped that this model can provide a solid foundation for developing quality staff in Islamic educational institutions so that they are able to make a positive contribution to the overall education of Muslims.